2018
DOI: 10.1038/s41598-018-23931-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and co-occurrence patterns in microbial communities under acute environmental stress reveal ecological factors fostering resilience

Abstract: Understanding the factors that modulate bacterial community assembly in natural soils is a longstanding challenge in microbial community ecology. In this work, we compared two microbial co-occurrence networks representing bacterial soil communities from two different sections of a pH, temperature and humidity gradient occurring along a western slope of the Andes in the Atacama Desert. In doing so, a topological graph alignment of co-occurrence networks was used to determine the impact of a shift in environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 53 publications
9
114
0
Order By: Relevance
“…The Atacama Desert is the oldest and driest desert on Earth. In recent years, it has become one of the principal areas for the study of microbial diversity, biogeochemistry and natural products potential 19,41 . Based on the particular soil scenario present in the Atacama Desert, two Gram-positive, rod-shaped and yellow-pigmented Microbacterium strains (CGR1 and CGR2) were isolated from soil samples collected from the Andes mountain range in the central region of the Atacama Desert (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Atacama Desert is the oldest and driest desert on Earth. In recent years, it has become one of the principal areas for the study of microbial diversity, biogeochemistry and natural products potential 19,41 . Based on the particular soil scenario present in the Atacama Desert, two Gram-positive, rod-shaped and yellow-pigmented Microbacterium strains (CGR1 and CGR2) were isolated from soil samples collected from the Andes mountain range in the central region of the Atacama Desert (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Electrical conductivity (EC) was determined in a 1:5 soil/water extract. Total elemental profiles from soluble soil extracts were determinate by Total Reflection X-ray Fluorescence (TXRF) 19 .…”
Section: Soils Condition Tolerance Assays and Elemental Content Ph Amentioning
confidence: 99%
“…Compared with that in the emerged areas, the bacterial co-occurrence network in the inundated areas was more complex, which could have been caused by the continuous hydrological connection in the inundated areas during the whole year 47,48 . Previous studies have also indicated that positive correlations between nodes in co-occurrence networks of desert soil bacterial communities could be the result of functional interdependencies among bacterial taxa under extreme environmental conditions [49][50][51] . In our study, high proportions of positive correlations between nodes in the two networks suggested the interdependencies among bacterial taxa under environmental disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the microbial community structure in the disease with the healthy can hence be achieved by construction of microbial association networks corresponding to each state, known as the 'case' and 'control' network respectively. This 'case' and 'control' networks can be further evaluated and compared based on their constituent network properties [21,[30][31][32][33][34]. However, meaningful insights can only be obtained when such pair of networks is comparable.…”
Section: Introductionmentioning
confidence: 99%